2019
DOI: 10.1556/030.66.2019.029
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vitro assays to study the effectiveness of antiparasitics against Acanthamoeba castellani trophozoites and cysts

Abstract: We aimed to compare LDH release assay, trypan blue and fluorescent stainings, and non-nutrient Escherichia coli plate assay in determining treatment efficacy of antiamoebic agents against Acanthamoeba castellanii trophozoites/cysts, in vitro. 1BU trophozoites/cysts were challenged with 0.02% polyhexamethylene biguanid (PHMB), 0.1% propamidine isethionate (PD), and 0.0065% miltefosine (MF). Efficacies of the drugs were determined by LDH release and trypan blue assays, by Hoechst 33343, calcein-AM, and ethidium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Even though the superiority of different drug screening assays has not been experimentally verified, the non-nutrient Escherichia coli plate assay has been suggested to function better than the LDH release assay, trypan blue and fluorescent staining. 56 The absorbance values between control curves (0) differ from each other in the testing of different inhibitors (range 0.5−1.9 in the inhibitor assay). Many factors can influence this.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the superiority of different drug screening assays has not been experimentally verified, the non-nutrient Escherichia coli plate assay has been suggested to function better than the LDH release assay, trypan blue and fluorescent staining. 56 The absorbance values between control curves (0) differ from each other in the testing of different inhibitors (range 0.5−1.9 in the inhibitor assay). Many factors can influence this.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
“…The challenge linked to SRB staining is that it only adheres to proteins in trophozoites, leading to the complete exclusion of cysts from the assay, thus limiting its ability to determine infections. Even though the superiority of different drug screening assays has not been experimentally verified, the non-nutrient Escherichia coli plate assay has been suggested to function better than the LDH release assay, trypan blue and fluorescent staining …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, we reported that the survival rates of drug-treated trophozoites/cysts determined by enzymatic-and dye-based viability assays might differ substantially from those yielded with the non-nutrient agar E. coli plate assay and proposed the latter test system as the gold standard for studying the treatment efficacy of drugs against Acanthamoeba spp. isolates [7]. In that study, we also observed that the off-label anti-amoebic drugs PHMB, PD, NM, and PVPI were more effective against the A. castellanii strain 1BU than the off-label anti-amoebic drugs CH, HD, DD, and MF under in vitro conditions; however, this was without providing a quantitative evaluation of the observed findings made with the non-nutrient agar E. coli plate assay [7].…”
Section: Introductionmentioning
confidence: 90%
“…isolates [7]. In that study, we also observed that the off-label anti-amoebic drugs PHMB, PD, NM, and PVPI were more effective against the A. castellanii strain 1BU than the off-label anti-amoebic drugs CH, HD, DD, and MF under in vitro conditions; however, this was without providing a quantitative evaluation of the observed findings made with the non-nutrient agar E. coli plate assay [7]. In the study presented here, we aimed to quantify the effectiveness of the off-label anti-amoebic agents PHMB, CH, HD, PD, DD, NM, MF, and PVPI in killing cysts of the A. castellanii strains 1BU (sequence type T4), 3ST (T4), and 9GU (T4), and the A. hatchetti strain 11DS (T6), under in vitro conditions.…”
Section: Introductionmentioning
confidence: 99%